Perbandingan Efektivitas Obat Antihipertensi Golongan ARB versus CCB terhadap Penurunan Tekanan Darah pada Pasien Hipertensi - Nuryanti, Eva; Wardhana, M. Fitra; Damayanti, Ervina; Triyandi, Ramadhan (CV. Jasa Sukses Abadi, 2024)
Hypertension is defined as a systolic blood pressure of more than 140 mmHg and a diastolic blood pressure of more than 90 mmHg. Hypertension is a degenerative disease that requires long-term treatment. Hypertension is a silent killer disease because it does not cause symptoms and is only detected during physical examination due to certain diseases so that it can be a major cause of morbidity and mortality. Hypertension management guidelines recommend the use of thiazide/ACEi/ARB/CCB diuretic class drug monotherapy. The purpose of this study is to determine the difference in effectiveness between Calcium Channel Blocker (CCB) and Angiostensin Receptor Blocker (ARB) antihypertensives in reducing blood pressure. The method used in this study is through literature review using a database through Google Schoolar and Pubmed with a time span of 2013-2023 using the PICO method with keywords or keywords tailored to the search topic and articles selected based on inclusion criteria. The results of the literature show that ARB and CCB antihypertensives have similar effectiveness in lowering blood pressure. CCB antihypertensives are vasculoselective. This can be beneficial because CCBs are able to reduce peripheral resistance without reducing heart function so as to reduce the incidence of stroke. However, the use of CCBs can cause edema while ARBs have renoprotective effects or effects that protect the kidneys.